Assessing Total Factor Productivity for Insurance Companies in Saudi Arabia Using DEA-Malmquist Approach - Ouertani, Mohamed Nejib (Journal of Posthumanism, 2025)
The present study measures the changes in both productivity and efficiency of insurance companies working in Saudi Arabia. To this end, the non-parametric frontier method Data Envelopment Analysis (DEA,) combined with the Malmquist index was employed to measure changes in productivity and efficiency of 26 Saudi insurers over the period 2019-2022. The study revealed that the changes in total productivity during the period is mainly imputed to the technological component. This increase was caused by a technological progress. But, the study raised a deterioration of the technical efficiency component for some insurers (10 companies). This result can be explained to a lack of managerial expertise and, in particular, poor resource management, which resulted in a decline in technical efficiency. Furthermore, the results revealed that the technological component, referring to the efforts made by insurers in terms of innovation, is more encouraging than those provided at the level of technical efficiency during the studied period. Finally, our study revealed that Saudi insurers can improve their practices and governance by introducing new innovative methods enabling an improvement in managing and governing more suitable the use of inputs to produce more outputs and to improving productivity of Saudi insurers.